VEGF-B-mediated myofiber types involved in high-fat diet-induced hyperglycemia through PKA-NFATs signaling pathway - Liu-liu Shi; Yu-ting Sun; Jia-nan Sun; Jing Yue; Wei Chen; Kun Meng; Long Chen; Chang-qing Hu; Rui Chen; Dong-sheng Sun; Cheng-bao Xu; Wei Yuan; et al. (Stem Cell Research & Therapy)
Abstract Background Hyperglycemia and insulin resistance are among the key phenotypes of obesity and type 2 diabetes (T2DM). Notably, skeletal muscle fiber-type composition is closely linked to insulin resistance. Vascular endothelial growth factor B (VEGF-B) has been shown to play an important role in T2DM. However, the effects of VEGF-B on myofiber types in individuals with obesity or T2DM remain unclear. This study aimed to investigate the effects and mechanisms of VEGF-B on myofiber-type formation and regeneration. Methods Male Vegfb (vascular endothelial growth factor B) gene knockout mice and wild-type C57BL/6 male mice were fed either a normal diet or a high-fat diet. Double immunofluorescence staining and RNA-seq of skeletal muscle tissue from these mice were used to evaluate the role of VEGF-B in myofiber type regulation. To investigate the effects of VEGF-B on myoblast differentiation, fusion, and type I slow-twitch fiber formation in vitro, we prepared a novel in vitro model by continuous single-dose administration of VEGF-B, which was matched with physiological conditions and high-fat diet-induced hyperglycemia in vivo. Results VEGF-B deficiency attenuated high-fat diet-induced loss of slow-twitch type I myofibers and improved hyperglycemia and insulin resistance in mice. Continuous low-concentration administration of VEGF-B isoforms (VEGF-B186 and VEGF-B167) enhanced myoblast differentiation, fusion and myotube formation in a dose-dependent manner, whereas higher concentrations inhibited these processes, with VEGF-B186 exhibiting more pronounced effects. Notably, elevated VEGF-B levels, particularly VEGF-B186, suppressed mainly slow-twitch type I myofiber formation. Mechanistic studies revealed that high-dose VEGF-B186 (100 ng/mL) reduced myoblast differentiation/fusion and slow-twitch fiber formation via PKA-NFAT-MyoG/MEF2C signaling. Furthermore, high-dose VEGF-B186 decreased the expression of glucose transporter type 4, glucose utilization, and mitochondrial function in a unique myoblast cell model, effects that were reversed by PKA activators and NFATc1/c2 overexpression. Conclusion These findings demonstrate that VEGF-B is a key regulator of myofiber type composition and metabolic homeostasis in the context of obesity or T2DM. The inhibitory effects of elevated VEGF-B186 on slow-twitch fiber formation and glucose metabolism underscore its pathological role in obesity-related metabolic dysregulation. These results support the therapeutic potential of targeting VEGF-B186—via inhibitors or monoclonal antibodies— for obesity and T2DM, which are characterized by slow-twitch fiber depletion.